2013
DOI: 10.1021/ac400105e
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Microcolumn-Based Process for Efficient Selection of RNA Aptamers

Abstract: We describe a reusable microcolumn and process for the efficient discovery of nucleic acid aptamers for multiple target molecules. The design of our device requires only microliter volumes of affinity chromatography resin—a condition that maximizes the enrichment of target-binding sequences over non-target-binding (i.e., background) sequences. Furthermore, the modular design of the device accommodates a multiplex aptamer selection protocol. We optimized the selection process performance using microcolumns fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…Each round involves aptamer binding to either soluble or immobilized targets and a method that separates target-bound from -unbound aptamers. Immobilized targets have included proteins (9,10), peptides (11,12) and metabolites (13–15), and immobilization plays an essential role in new microfluidic SELEX technologies (10,16). Optimization of SELEX in these situations requires that we understand whether cooperative binding might change effective affinities, and if so, how.…”
Section: Introductionmentioning
confidence: 99%
“…Each round involves aptamer binding to either soluble or immobilized targets and a method that separates target-bound from -unbound aptamers. Immobilized targets have included proteins (9,10), peptides (11,12) and metabolites (13–15), and immobilization plays an essential role in new microfluidic SELEX technologies (10,16). Optimization of SELEX in these situations requires that we understand whether cooperative binding might change effective affinities, and if so, how.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 More recently, nucleic acid aptamers have been introduced as novel recognition elements. [27][28][29][30][31] Aptamers are short artificial DNA and RNA sequences selectively chosen by their extremely strong binding affinity to their target proteins through a process called Systematic Evolution of Ligands by Exponential Enrichment (SELEX). In the SELEX process, an extremely large pool of oligonucleotides of different sequences is incubated with the protein target of interest.…”
Section: Preliminary Results and Discussionmentioning
confidence: 99%
“…The use of microcolumns was optimized for maximum enrichments of aptamers, revealing critical target concentrations that could be explained by geometric constraints for steric hindrance. 60,61 This concentration as well as the small column volume reduce the amount of target needed by several orders of magnitude. Furthermore, tests that varied the flow rates resulted in enrichment trends that scaled oppositely from the time-dependent kinetic binding model where the concentrations of unbound and bound molecules are also dependent upon their position x along the column…”
Section: Filtering Aptamers: Miniaturized Affinity Chromatographymentioning
confidence: 99%
“…Recent studies have shown that in certain technologies, many of the core and intuitive assumptions of the SELEX model and basic binding kinetics are not well supported by the binding results. 36,37,[60][61][62]66,67,75 This is likely due to the added complexity of the more sophisticated technologies and immobilization schemes used. Selection techniques are currently evaluated primarily on the number of cycles needed and/or on the binding affinity of the resulting aptamer.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%